In the name of the father-in-law: Pastoralism, patriarchy and the sociolinguistic prehistory of eastern and southern Africa. (19th July 2019) - Fleming, Luke; Mitchell, Alice; Ribot, Isabelle
Abstract : In a range of eastern and southern African language communities, stretching from Ethiopiato the Cape, married women are enjoined to avoid the names of members of theirhusband's family as well as (near-)homophones of those names, and to replace tabooedvocabulary with substitute words. Although in-law name avoidance is a globalphenomenon, the daughter-in-law speech registers thus constituted are unusual in theirlinguistic elaboration: they involve avoidance not only of names and true homophones ofnames but also an array of words whose only relation to tabooed names is phonologicalsimilarity. We provide an overview of the distribution and convergent social and linguisticcharacteristics of these registers and then examine one register more closely, namely, thatof Datooga of Tanzania. To tease apart the layers of causality that converge upon thisparticular sociolinguistic pattern, we consider archaeological, ethnological, sociolinguisticand genetic lines of evidence. We propose that any partial diffusion of in-law avoidancepractices has been complemented by a complex of sociocultural factors motivating theemergence of this pattern at different times and places across the African continent. Thesefactors include pastoralism, patrilineal descent ideologies and norms of patrilocal postmaritalresidence paired with cattle-based bridewealth exchange.